A new species of Catapiestus Perty, 1831 from China (Coleoptera, Tenebrionidae, Cnodalonini) - Shulin Yang; Juan Guo (ZooKeys, 2018)
A new species of the genus Catapiestus Perty, 1831 (Coleoptera, Tenebrionidae, Cnodalonini), C. bispinosus, is described from Leigonsan National Nature Reserve, Leishan County, Guizhou, China. The identification key by Lang and Ren for the species of Catapiestus is modified.